Awareness of Islam in the Post-9/11 American Workplace - Belal A. Kaifi (International Institute of Islamic Thought, 2012)
Political unrest in Islamic nations, worldwide terrorist attacks, and the western media’s coverage of these events might be contributing to a distorted and biased perception of Muslims. This article analyzes the responses of vocational college instructors to a nineteenquestion survey regarding Islam. It was intended to evaluate the 100 participants’ knowledge and understanding of Islam in the aftermath of the 9/11 tragedy. An evaluation of their answers suggested that the majority of them lacked basic knowledge about Islam. Although some of the responses indicated that the instructors would treat Muslim students with sensitivity, only a few understood how to respond to certain classroom situations. The results show that vocational instructors urgently need diversity training programs that focus on the similarities, as opposed to the minor differences, of views and religions. Interpersonal training should address the importance of respecting differences in the workforce by emphasizing professionalism and conflict management techniques. Training implications are presented and explored.